THE FUNCTIONAL RESPONSIBILITIES OF TEACHERS AND VARIOUS SPECIALISTS IN INCLUSIVE EDUCATION - Kassymova, A.G.; Koszhanova, A.G. (publisher of Kostanay state pedagogical university, 2020)
he article says that one of the main tasks of the educational institutions’ teachers work in the inclusive education context is the quality management of the regulated process of including a child with special educational needs and his family in the general educational environment. And one of the main steps in this direction for changing social conditions should be the training of all participants in the educational process, and the teacher himself, at first.
Keywords: a child with special educational needs; a person with visual impairment; a person with hearing impairment;; a disabled student; a child with physical disabilities; a boy with intellectual disabilities; a girl with learning difficulties